2011
DOI: 10.1161/hypertensionaha.111.172924
|View full text |Cite
|
Sign up to set email alerts
|

How to Best Assess Blood Pressure?

Abstract: See related article, pp 1087-1093I t is half a century since high blood pressure (BP) measured in the doctor's office has been proved to be a strong predictor of cardiovascular morbidity and mortality. However, it soon became clear that multiple factors can significantly affect the BP measurement result (Table 1) and may thereby have considerable impact on its prognostic ability.Despite the intensive research with almost 120 000 PubMed papers on issues related to BP monitoring, the question "how to best assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
4

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 11 publications
1
18
0
4
Order By: Relevance
“…Although day-to-day BPV is an index of BPV during the medium term, BPV within a 24-h period assessed by ABPM and visitto-visit variability assessed by clinic BP are indices of BP instability during the short and long terms, respectively. 16 There is no consensus on a single definition of the method to evaluate day-to-day BPV. Kikuya et al 4 evaluated measuring BP once every morning and evening to calculate day-to-day variability, while Johansson et al 17 evaluated measuring BP twice every morning and evening.…”
Section: Discussionmentioning
confidence: 99%
“…Although day-to-day BPV is an index of BPV during the medium term, BPV within a 24-h period assessed by ABPM and visitto-visit variability assessed by clinic BP are indices of BP instability during the short and long terms, respectively. 16 There is no consensus on a single definition of the method to evaluate day-to-day BPV. Kikuya et al 4 evaluated measuring BP once every morning and evening to calculate day-to-day variability, while Johansson et al 17 evaluated measuring BP twice every morning and evening.…”
Section: Discussionmentioning
confidence: 99%
“…How to best assess blood pressure average and variability is still a matter of the ongoing debate on the clinical value of blood pressure. 94) We must pay more careful attention focused on hypertension with blood pressure fluctuation. In order to predict the future atherosclerosis and cardiovascular events in subjects with hypertension, the adequate assessment of endothelial function is one of the most reliable markers.…”
Section: Discussionmentioning
confidence: 99%
“…However, these different components of blood pressure variability may reflect different mechanisms, are likely to provide different information on cardiovascular regulation, and might have different clinical implications that are still poorly understood. 1 The assessment of office blood pressure variability in repeated visits, although successful in the context of outcome trials such as the ASCOT 2,3 and the NHANES 4 studies, appears to be impractical for routine clinical use; first, because of poorly standardized office measurements and, second, because of the long time required for multiple visits. Regarding the 24-h ambulatory monitoring, the results of the ASCOT study and the IDACO database have been rather disappointing, 2,3,10 but further studies with more frequent readings must be performed.…”
Section: The Optimal Methods For Assessing Blood Pressure Variabilitymentioning
confidence: 99%
“…1 Recently, blood pressure variability has gained significant attention due to the publication of retrospective analyses of the Anglo-Scandinavian Cardiac Outcomes Trial Blood Pressure Lowering Arm (ASCOT-BPLA) data by Rothwell et al These analyses showed, first, that systolic blood pressure variability and the maximum systolic blood pressure are strong predictors of stroke independent of the mean blood pressure 2 and, second, that different antihypertensive drugs might differently affect blood pressure variability, influencing their contribution to cardiovascular protection. 3 The NHANES study confirmed the relationship between systolic blood pressure variability and an allcause mortality in the general population.…”
Section: Office Blood Pressure Variabilitymentioning
confidence: 99%
See 1 more Smart Citation